THE CONTENTS SELECTION IN SCHOOL PHYSICAL EDUCATION. (Fiep Bulletin - online, 2013)
This study has as a central purpose, identify the main contents that are used by teachers in physical education classes in the final years of elementary education in public schools from Erechim, RS. It has both quantitative and qualitative character and it aimed to collect data that allowed us to map the contents and criteria that are being included in the course program in schools from Erechim. 100% of the teachers that work with physical education in the final years of elementary schools were interviewed. Data points that we are developing a physical education that has strong tendencies to sports, since 90% of the teachers use mainly traditional sports to evolve the course in the scholastic context. The study pointed that teachers determine which contents are taught based on student's preference or materials' availability and school's space. Moreover, we noticed that physical education's theory is underutilized and when it happens to be used, it basically approaches to issues such as history, rules, specific techniques and tactics of sports, leaving aside issues such as contextualization and problematization  of sports' social function, its relation with health, and other possibilities.
Keywords: Body culture of movement; Acquirements; Sports.